Evaluation of argon plasma coagulation in healing of a solitary rectal ulcer in comparison with conventional therapy: a randomised controlled trial - Farzad Jassemi Zergani; Ali Akbar Shaiesthe; Eskandar Hajiani; Jalal Hashemi; Rahim Masjedizadeh; Vaheid Sebghatollahei; Pejman Alavinejad; Ahmad Kadkhodaei; Kambeiz Akhavan; Saeid Seyyedian (Gastroenterology Review)
Introduction: Argon plasma coagulation (APC) has been reported to be effective in the treatment of solitary rectal ulcer syndrome (SRUS). However, it has not appeared to be effective in healing ulcers. Aim : This study aimed at assessing the effectiveness of APC in controlling rectal ulcer-induced bleeding, and at examining the ultimate effect of this approach in healing these lesions. Material and methods : This randomised, controlled trial was conducted on 99 patients with SRUS. Patients were randomly enrolled into two groups of APC therapy (intervention) and conventional therapy (control). The control group (n = 58) received a high-fibre diet, laxatives, behaviour therapy, and sucralfate enemas, and the intervention group (n = 41) were treated with APC plus conventional therapy; in fact they received directed and focused argon gas in addition to a high-fibre diet and laxatives. Results: Responses to treatment in the control group and in the APC-receiving group were 29.3% and 75.6%, respectively. The continuation of ulcer healing after 3 months in the control group was 10.3%, and it was 70.7% in the APC-treated group. There was a significant statistical difference between the two groups (p < 0.004), i.e. bleeding was controlled more frequently in the group receiving APC plus conventional therapies than in the group receiving only the conventional therapies. However, the results showed no statistically significant difference between the two groups in terms of pain relief (p < 0.36). Conclusions : Argon plasma coagulation not only controlled bleeding in patients with SRUS, but also, in comparison with the conventional methods of treating SRUS, led to healing and continuation of healing of rectal ulcers.